2002
DOI: 10.1029/2001jd000449
|View full text |Cite
|
Sign up to set email alerts
|

Loss of isoprene and sources of nighttime OH radicals at a rural site in the United States: Results from photochemical models

Abstract: [1] A one-dimensional Lagrangian model for atmospheric transport and photochemistry has been developed and used to interpret measurements made at Pellston, Michigan, during the summer of 1998. The model represents a moving vertical column of air with vertical resolution of 25 m near the ground. Calculations have been performed for a series of trajectories, with representation of emissions, vertical mixing, and photochemistry for a 3-day period ending with the arrival of the air column at Pellston. Results have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 48 publications
(121 reference statements)
8
53
3
Order By: Relevance
“…1b shows the hourly means of these measured and modeled fluxes as well as the difference (between measured and modeled fluxes) during these 20 days. The model generally overpredicts the flux during the mornings and underpredicts the fluxes in the afternoons, which is a similar finding as that reported by Sillman et al (2002).…”
Section: Isoprenesupporting
confidence: 88%
“…1b shows the hourly means of these measured and modeled fluxes as well as the difference (between measured and modeled fluxes) during these 20 days. The model generally overpredicts the flux during the mornings and underpredicts the fluxes in the afternoons, which is a similar finding as that reported by Sillman et al (2002).…”
Section: Isoprenesupporting
confidence: 88%
“…In their model results, the observed loss of isoprene was mainly caused by the vertical diffusions. Nevertheless, Sillman et al (2002) also pointed out that in a shallow layer near the surface, the chemical reaction with OH might be important as diagnosed by Faloona et al (2001) for the same campaign. Furthermore, in the shallow nocturnal boundary layer, weak isoprene emitters could still play a role, such as emissions from urban traffic (Lee and Wang, 2006;Liu et al, 2008) and biogenic emissions under dark conditions, which are usually neglected compared to daytime emissions (Guenther, 1999;Shao et al, 2001).…”
Section: Unexpectedly Large Nighttime Oh Concentrationsmentioning
confidence: 88%
“…Besides its chemical removal by OH, isoprene is also subject to transport, for which we have insufficient knowledge with respect to the spatial/vertical isoprene distribution around the measurement sites. As diagnosed by Sillman et al (2002) for the Michigan forested areas, the nighttime loss of isoprene can be attributed to three factors: chemical reaction with OH, vertical diffusion, and advection. In their model results, the observed loss of isoprene was mainly caused by the vertical diffusions.…”
Section: Unexpectedly Large Nighttime Oh Concentrationsmentioning
confidence: 99%
“…Although nighttime decays of surface-level isoprene are well-documented (Hurst et al, 2001;Trainer et al, 1991), their interpretation is often complicated by the competing effects of chemistry and transport, particularly within shallow nocturnal boundary layers . For example, measurements at forested sites impacted by urban NO x emissions have in several instances found evening isoprene loss rates consistent with consumption by NO 3 radicals (Starn et al, 1998;Steinbacher et al, 2005;Stroud et al, 2002), while analysis of data from more remote locations have shown the importance of either transport or, possibly, additional oxidants such as nighttime OH (Biesenthal et al, 1998;Sillman et al, 2002). Analyses of surface level NO 3 measurements in regions downwind of forested areas have shown that biogenic VOCs, including isoprene and monoterpenes, consume a significant fraction of NO 3 radicals (Aldener et al, 2006;Ambrose et al, 2007;Geyer et al, 2001;McLaren et al, 2004).…”
Section: Introductionmentioning
confidence: 99%